A sistematização da lógica interna do futsal a partir da praxiologia motriz - Follmann, Natiele (2019)
Futsal is a motor practice that is increasingly present at school and in several other training spaces, constituting an important part of the sport activity of children, youth and adults. The Motor Praxiology is a theory that allows unveils the operating logic of motor practices. The objective of this research is to systematize the elements of Futsal's internal logic, based on the Motor Praxiology, to contribute to the teaching-learning process. Through a theoretical research, it was made a historical rescue of the sport, dealing specifically with how Futsal came about and what were the main evolutions in its rules. In order to analyze the scenario of scientific publications on the sport, a survey was conducted in eight online journals. From this, we realized the need for studies that deal with Futsal and Motor Praxiology, as well as the knowledge of the teaching-learning process of this sport. When considering praxiological knowledge, this proposal becomes fundamental to produce a basis that assists the pedagogical work with Futsal in various fields and using this knowledge in teaching is fundamental to improve the understanding of the game. Futsal is a sport with cooperation-opposition motor interactions, where players aim to reach the opposing goal by making the goal, while facilitating actions for their teammates and making it difficult for opponents. Understanding the internal logic of the game begins with knowing the main general rules of the game and how the players, from these, can relate themselves to space, time, material and other players. In order to achieve the proposed systematization, it was based on the analysis tools of the Motor Praxiology, the CAI Classification System and the Ludomotor Universals. When the systematization is performed, new possibilities for teaching the game are presented. The teaching will be based on the game as a whole, where the tactical and technical needs derive from each other and happen with meaning. To select what and how to teach, the teachertrainer needs in-depth knowledge. This work aims to reach those responsible for the various formative spaces and, thus, bring together the scientifically produced knowledge to the empirical knowledge acquired on the “floor of practice”.